PROSES TRANSFORMASI DIGITAL LAYANAN CUKAI DI DIREKTORAT JENDERAL BEA DAN CUKAI - Nugroho, Arief Seno; Himawan, Tedy (Simposium Nasional Keuangan Negara, 2025)
The Third Millennium Era (Piliang, 2020) is a period where changes in the structure of social relations and habits in society arise due to technology (Susarla et al., 2012), these changes in society's mobility patterns should be a concern for the Government as a policy maker. One of the global challenges that is of concern to the Government is the response to the development of digitalization, because digital transformation in the public sector is related to the government's role in directing how technology is used by the public and shaping its activities as a consequence of the use of technology. The Directorate General of Customs and Excise (DJBC) is a central government agency part of the Ministry of Finance which is currently continuously making improvements by using digitalization in public services in the context of bureaucratic reform and institutional transformation so that it is able to receive the "Top Digital Implementation 2022 Level Stars 5 &" award. Top Leader on Digital Implementation 2022”. With the achievements and processes that have been carried out by DJBC, this research aims to see how the digital transformation process is and at what stage the DJBC digital transformation process is currently. This research uses a descriptive qualitative approach with primary data in the form of interviews, field observations, and supporting documentation on the implementation of digitalization of excise services involving the Evaluation and Application System Development Team in the Excise Sector and the Excise Application System Development Team. The results of the analysis show that the digital transformation process of excise services has been carried out since it was still using writing on forms, a recital tool system, computerization, until now it has been carried out in an automated manner. The achievements of this process when referred to in the OECD framework (2016) are in the transition from the second stage to the third stage, namely the e-government stage towards digital government. At this stage it can be seen from the focus of changes that have been achieved in the purpose of use, involvement, main activities, and individual service. Author believes that the achievements of this process can still be developed with the development of ExSIS 4.0 which is currently being carried out.